Scientific and methodological principles of land distribution (re-distribution) on the basis of designated purposes and types of land use - Dorosh, Y.; Dorosh, O.; Kharytonenko, R.; Dorosh, A.; Zastulka, O. (Land Management, Cadastre and Land Monitoring, 2020)
The normative legal acts and scientific publications on the distribution (redistribution) of land by purpose and types of use are analyzed on the example of land uses of institutions and enterprises of the National Academy of Agrarian Sciences of Ukraine (hereinafter - NAAS). It is established that in the current legislation there is no type of documentation on land management, concerning the decision of questions of distribution (redistribution) of land by types of use. To take into account the specifics of land use by the NAAS institutions and enterprises, which have land plots, research fields, nurseries, valuable lands for scientific research, which should be taken into account when developing documentation on land management. The necessity of introducing scientific justification for determining the purpose and type of use as a section in the land documentation documentation is proposed. Keywords: land management, scientific justification, land distribution (redistribution), research land use.